Return-to-play protocols following sport-related concussion in NCAA gymnastics - Horner, A.; Root, H. J.; Valovich McLeod, T. C. (Journal of Athletic Training, 2019)
Context: Gymnastics requires skills of varying diffi culty on multiple apparatuses including a combination of linear and rotational movements with fl ight elements, which increases the risk of falls and surface contact. This poses a unique threat of sustaining a sportrelated concussion (SRC) as well as challenges with returning athletes to sport. Little is known about return-to-play (RTP) protocols following concussion at the collegiate level. The purpose of this study was to determine the current practices of athletic trainers (ATs) regarding concussion management and RTP in collegiate gymnastics. Methods: A crosssectional online survey design was used to assess concussion management practices and return to gymnastics protocols among athletic trainers assigned to NCAA gymnastics programs. The survey was validated by a panel of medical and gymnastics experts for face validity. The survey consisted of 5 sections: institution demographics, athletic training services demographics, concussion demographics, baseline concussion testing practices, and return to gymnastics protocol. Question types included multiplechoice, 4-point Likert scale items, and multiitem questions. The survey took approximately 10 minutes to complete. They survey was sent to ATs with listed affi liation to the gymnastics team(s), but if sport assignment was not included online, emails were sent to the head athletic trainer. Schools were excluded if no contact information was available on the website. Frequencies and percentages were reported. Results: Eightynine ATs were contacted, 39 ATs (17 male, 16 females, 5 anonymous) completed the survey (response rate= 43.82%), with the majority of those working at the division I level (69.2%, n=27) Journal of Athletic TrainingVolume 54 o Number 6 (Supplement) June 2019 S-311and with female teams (69.2%, n=27). Respondents reported 22.3±10.3 (range 10-60) gymnasts participating per team. ATs providing care for female gymnasts reported fiftyone concussions (average=1.7±1.7, range 0-8) during the 2017-18 competition season, with the majority occurring on uneven bars (n=32/51, 54.23%) and fl oor exercise (n=8/51, 15.68%). ATs providing care for male gymnasts reported 31 concussions (average=3.44±6.63, range 0-12), with high bar (n=16/31, 51.61%) and rings (n=9/31, 29.03%) resulting in the highest number of concussions. Only 46% (n=18/39) of the ATs reported having a gymnasticsspecific RTP protocol. Onefifth (n=8/39) indicated they experience challenges with progressing gymnasts through different movement planes, particularly fl ight and release skills. Of those with gymnasticsspecific RTP protocols most described a progression beginning with aerobic exercises, progressing to strength-based skills, simple rotations (without dismounts), complex rotations, and fi nally dismounts, beginning with landing in the pit to mats, to normal fl oor. Conclusions: We found higher reporting number of concussions within NCAA gymnastics programs than had been reported in previous years. Less than half of the respondents reported having gymnastics specifi c RTP protocol and many faced challenges in knowing how to progress gymnasts. Many reported good collaboration with their directing physician and the coaching staff to help determine the appropriate skill progressions.